Hypotensive effects of resistance exercise with continuous and intermittent blood flow restriction - Gabriel Rodrigues Neto; Jefferson da Silva Novaes; Michel Gonçalves; Gilmário Ricarte Batista; Rosa Maria Soares Costa de Mendonça; Humberto Miranda; Giovanni da Silva Novaes; Maria do Socorro Cirilo-Sousa
Abstract The aim of this study was to compare the acute effects of low-intensity (LI) resistance exercise (RE) with continuous blood flow restriction (CBFR) and intermittent blood flow restriction (IBFR) on systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP). After a one-repetition maximum test, 10 normotensive recreationally trained men performed three experimental protocols. In the three RE protocols, increases in SBP, DBP, and MAP were observed immediately after exercise, but the effect sizes (ESs) were greater for the LI + CBFR and high-intensity protocols. There were hypotensive effects on SBP, DBP, and MAP in all three protocols; however, the effects on MAP lasted longer for the LI + IBFR and LI + CBFR protocols. These long-lasting hypotensive effects on DBP and MAP occurred in all three protocols. Thus, we conclude that the post exercise hypotensive effects on SBP, DBP, and MAP appear to occur in all three RE protocols, with the effect on SBP being longer in the LI + IBFR and LI + CBFR protocols.